Consumer protection and competition policy (UN New YorkUS, 2012)
Addresses the interactions between competition policy and consumer policy to provide an overview for the topics to be further discussed during the first Ad Hoc Expert Meeting on Consumer Protection in July 2012. Compares the objectives of the two policies. Discusses the interaction in the two types of markets, viz. the imperfect and the other where high costs are generated in securing informaton about competing offers; moves to insurance and savings products, remittances, conterfeit medicines and unsafe consumer products.
Note by the UNCTAD Secretariat.